1.x的2006次幂乘以y的2007次幂=x的2006次幂乘以y的2006次幂乘以y
因为x=√3+√2 y=√3-√2(√是根号)
所以
x的2006次幂乘以y的2006次幂乘以y
=【(√3+√2)*(√3-√2)】的2006次幂*(√3-√2)
=1的2006次幂*(√3-√2)
=√3-√2
2.1除以根号1-x=√(1-x)除以(1-x)
因为分母不能为0
所以x≠1
因为√(1-x)
所以1-x>0
所以x<1
3.x=1
1.
(2-√2) (2-√2)*(1-√3) -4-2√3-√2 -2(2+√3)-√2
------------- = ---------------------------- = -------------------------- = -----------------------------
(1+√3) (1+√3)*(1-√3) -2 -2
=2+√3-√2
2.根号(6+根号20)=根号(6+2√5)
√5*(√6+2√5) √30+10 5√6+10√5
= -------------------------- = ---------------- = -------------------------
√5 √5 5
3
1
(√2+1)- -------------- = 2
(√2+1)
原式=2的2006次幂÷2√2的1336次幂
2的2008次幂 √2的2010次幂
= -------------------------- = ----------------------------- =√2的672次幂=2的336次幂
2√2的1336次幂 √2的1338次幂
4(ab-2)²>=0 所以,a-1=0 a=1所以b=2
1/ab+1/(a+1)(b+1)+1/(a+2)(b+2)+.+1/(a+2008)(b+2008)=1-1/2+1/2-1/3…………+1/2009-1/3000=1-1/3000=2999/3000